Field‐aligned currents' scale analysis performed with the Swarm constellation. Issue 1 (7th January 2015) - Lühr, Hermann; Park, Jaeheung; Gjerloev, Jesper W.; Rauberg, Jan; Michaelis, Ingo; Merayo, Jose M. G.; Brauer, Peter
Abstract We present a statistical study of the temporal‐ and spatial‐scale characteristics of different field‐aligned current (FAC) types derived with the Swarm satellite formation. We divide FACs into two classes: small‐scale, up to some 10 km, which are carried predominantly by kinetic Alfvén waves, and large‐scale FACs with sizes of more than 150 km. For determining temporal variability we consider measurements at the same point, the orbital crossovers near the poles, but at different times. From correlation analysis we obtain a persistent period of small‐scale FACs of order 10 s, while large‐scale FACs can be regarded stationary for more than 60 s. For the first time we investigate the longitudinal scales. Large‐scale FACs are different on dayside and nightside. On the nightside the longitudinal extension is on average 4 times the latitudinal width, while on the dayside, particularly in the cusp region, latitudinal and longitudinal scales are comparable.